Editor’s Note. - García Díaz, Dr. Vicente; Wu, Prof. Shaofei (International Journal of Interactive Multimedia and Artificial Intelligence, 2020)
The International Journal of Interactive Multimedia and Artificial Intelligence - IJIMAI (ISSN 1989 - 1660) provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances on Artificial Intelligence (AI) tools or tools that use AI with interactive multimedia techniques.